An Optical Grooming Switch for High-Speed Traffic Aggregation in Time, Space and Wavelength - Vorreau, Philipp (Karlsruhe Series in Photonics & Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2010)
In this book a novel optical switch is designed, developed, and tested. The switch integrates optical switching, transparent traffic aggregation/grooming, and optical regener-ation. Innovative switch subsystems are developed that enable these functionalities, including all-optical OTDM-to-WDM converters. High capacity ring interconnection between metro-core rings, carrying 130 Gbit/s OTDM traffic, and metro-access rings carring 43 Gbit/s WDM traffic is experimentally demonstrated. The developed switch features flexibility in bandwidth provisioning, scalability to higher traffic volumes, and backward compatibility with existing network implementations in a future-proof way.